2022
DOI: 10.1155/2022/7740210
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Adsorption Characteristics of Mo-Doped Graphene on the Decomposition Products of SF6 Substitute Gas Based on First-Principle Calculations

Abstract: C4F7N, C5F10O, etc., as new environmental-friendly alternative gases decompose under partial discharge and produce a series of products such as CO, CF4, C2F6, C3F8, CF3CN, C2F5CN, and COF2. Based on the first-principles calculation method of density functional theory (DFT), the adsorption characteristics of intrinsic state graphene and Mo-doped graphene adsorbing SF6 and its substitute gas decomposition products are calculated and analyzed. By comparing the adsorption energy, adsorption distance, density of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Regardless of computing platform and configurations, most established sensing substrates with metal or metal oxide dopants displayed large E ads and Q t upon SOF 2 and SO 2 F 2 molecules, which usually experience chemical bond fracture during adsorption (Figure a). Although higher E ads and Q t possibly indicate a better response property, it increases the difficulty of sensor recovery. According to the theoretical desorption formula, τ = v 0 –1 exp­(− E ads /( kT )), where τ is the desorption time, v 0 is the attempt frequency, k is the Boltzmann constant, and T is the temperature, the desorption time increases exponentially with the increase of E ads at a fixed temperature. Therefore, blindly pursuing high E ads and Q t will expose the sensors to the risk of poisoning and short lifespan.…”
Section: High Performance Designs For Industrial Gas Sensing Applicationmentioning
confidence: 99%
“…Regardless of computing platform and configurations, most established sensing substrates with metal or metal oxide dopants displayed large E ads and Q t upon SOF 2 and SO 2 F 2 molecules, which usually experience chemical bond fracture during adsorption (Figure a). Although higher E ads and Q t possibly indicate a better response property, it increases the difficulty of sensor recovery. According to the theoretical desorption formula, τ = v 0 –1 exp­(− E ads /( kT )), where τ is the desorption time, v 0 is the attempt frequency, k is the Boltzmann constant, and T is the temperature, the desorption time increases exponentially with the increase of E ads at a fixed temperature. Therefore, blindly pursuing high E ads and Q t will expose the sensors to the risk of poisoning and short lifespan.…”
Section: High Performance Designs For Industrial Gas Sensing Applicationmentioning
confidence: 99%
“…The potential of two-dimensional (2D) materials as adsorbent materials for environmental protection is significant due to their high surface area, controlled interlayer bonding, specific binding capacity, chemical stability and sensitivity [13,14]. In recent years, a variety of 2D materials, including 2D sulfur compounds [2,15], ZnO [16], C3N [17], MXenes [18], graphene [19] and the group III-V nitrides [20] have demonstrated high efficacy in the detecting and capturing harmful gases. For instance, Hu et al [21] investigated the adsorption characteristics of NH3, CO and NO2 on SnS monolayers, and the results showed that there exists a significant adsorption effect of NO2 on the SnS monolayers.…”
Section: Introductionmentioning
confidence: 99%